Anxiety in teachers in the COVID-19 context of two universities in the Ica region - Jurado-Enríquez, Elizabeth; Vargas-Prado, Kelly; Jurado-Retamoso, Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
University teachers are a fundamental part of the process of academic and personal training of future professionals. The methodology is quantitative, basic at a comparative level where the difference between the levels of anxiety in the teachers of both universities is analysed. It has a comparative descriptive design and its method was hypothetical deductive.The sample consisted of 57 teachers from two private universities in the Ica region in Peru, chosen by non-probabilistic sampling. The instrument was the Beck Anxiety Inventory (BAI) composed of 21 items applied through a virtual, anonymous, confidential, and voluntary form. The results showed that 73.7% of teachers have no presence of anxiety, 21.1% have a mild level and 5.3% have a moderate level. It was found that there are no significant differences in anxiety between the teachers of these two universities; having obtained a p-value of 0.275. The conclusion the highest percentage of teachers of both universities do not show symptoms related to anxiety. Finally, future research is pending to continue comparing anxiety levels.